Gonioreflectometer for measuring 3D spectral BRDF of horizontally aligned samples with traceability to SI. (1st April 2022) - Lanevski, Dmitri; Manoocheri, Farshid; Ikonen, Erkki
Abstract: Present article describes a 3D gonioreflectometer developed at Aalto University for the measurement of spectral bidirectional reflectance distribution function (sBRDF) of horizontally aligned samples, needed to study sBRDF of sand from satellite calibration test sites. The new set-up incorporates three motorized arms that allow to measure in- and out-of-plane sBRDF. Illumination of the sample is provided by a supercontinuum laser coupled with laser line tunable filters and detection is performed with two types of photodiodes (Si and InGaAs) enabling collection of sBRDF in the spectral range from 450 nm to 1700 nm. The instrument is operated in the relative mode and its traceability to SI is achieved with the help of a 2D absolute reference gonioreflectometer available at Aalto University. The calibration procedure as well as system's uncertainty estimation are described. The performance of the 3D gonioreflectometer is validated by measurements of a ceramic diffuse reflectance sample.